Respuesta :

The answer is:  z² .
__________________________
Given: (x÷(y÷z))÷((x÷y)÷z) ;  without any specified values for the variables; 
_______________________
we shall simplify.
___________________
We have: 
__________
(x÷(y÷z))  /  ((x÷y)÷z) .
_____________________________________
Start with the first term; or,  "numerator":  (x÷(y÷z)) ;
_____________________________________
x  ÷ (y / z) = (x / 1) * (z / y) = (x * z) / (1 *y) =  [(xz) / y ] 
_____________________________________
Then, take the second term; or "denominator":
_____________________________________
((x ÷ y) ÷z ) = (x / y) / z =  (x / y) * (1 / z) = (x *1) / (y *z) = [x / (zy)]
_________________________________________
So (x÷(y÷z))  /  ((x÷y)÷z)  = (x÷(y÷z)) ÷  ((x÷y)÷z) =

 [(xz) / y ] ÷ [x / (zy)]  = [(xz) / y ] /  [x / (zy)] =
                                                                    [(xz) / y ] * [(zy) / x] ;
_______________________________________
                               The 2 (two) z's "cancel out" to "1" ; and
                                  The 2 (two) y's = "cancel out" to "1" ; 
______________________________________________
And we are left with: z * z = z² .  The answer is:  z² .
______________________________________________